A term vaginal delivery by a patient with traumatic tetraplegia: A case report. Issue 16 (April 2018) - Yao, Changfang; Xu, Yongjuan; Dai, Li; Lv, Yan; Xu, Xiaoli; Ye, Wenfeng
Abstract: Rationale: About 60, 0000 people are involved in traffic accident each year in China and spinal cord injury (SCI) often occurs. Pregnant women with paraplegia is rare, and they face higher risk during pregnancy and childbirth. Patient concerns: We report a case of a 35-year-old patient with SCI, who had vaginal forceps delivery at 38 weeks and 5 days of gestation. Diagnoses: The patient was diagnosed with term pregnancy with traumatic tetraplegia. Interventions: A vaginal forceps delivery was performed at 38 weeks and 5 days of gestation. Outcomes: A vaginal forceps delivery of the patient was smooth. After delivery the patient recovered quickly, her vaginal blood was less, blood pressure was favoring. Lessons: This study presents a case with traumatic tetraplegia during pregnancy. We suggest that regular prenatal care is necessary.